The biological complication of implant abutment materials. A systematic review and meta-analysis - Mokhtar, M. A.; Elnagar, G.; Saleh, M.; Radwan, M. M. (Journal of Osseointegration, 2018)
Aim The goal of this review was to identify the biological complication of implant abutment materials in relation to alveolar bone around implant-supported superstructure. Methodology An electronic database search and a further manual search were directed to select RCTs, and cohort studies that give evidence about different abutment materials complication. Pocket depth, amount of rescission and crestal bone loss were attributed to alveolar bone loss. Results Fourteen clinical studies were selected from an initial search of 107 studies and the extraction of the analysis data were tabled according to complication output. Pocket probing depth were documented in eight studies, PPD around Zirconium implant abutments was 3.2 mm versus 3.4 mm for Titanium abutments. Five studies examined the recession index for Zirconium and Titanium implant abutments. The RI ranged from 0 to 0.4 at Titanium implant abutments and 0 to 0.3 at Zirconium implant abutments. Alveolar bone loss around Zirconia abutments was reported to differ from 0.2-1.48 mm and 0.3-1.43mm at Titanium abutments. Conclusion The data reported in this systematic review did not give an evidence for the complication regarding all ceramic versus metallic implant abutment. However, it can be concluded that the assessment of the randomized clinical trials did not provide an absolute decision for the choice of ceramic or metallic as implant abutment material in relation to alveolar bone response. The meta-analysis presented a statistically significant difference between abutment material with superiority for the all ceramic abutments over metallic abutment providing a favorable response of Marginal Bone Loss, but non-statistically significant regarding Pocket Probing Depth and Recession Index of soft tissue.